Contribution of energetic and heavy ions to the plasma pressure: The 27 September to 3 October 2002 storm. Issue 9 (19th September 2017) - Kronberg, E. A.; Welling, D.; Kistler, L. M.; Mouikis, C.; Daly, P. W.; Grigorenko, E. E.; Klecker, B.; Dandouras, I.
Abstract: Magnetospheric plasma sheet ions drift toward the Earth and populate the ring current. The ring current plasma pressure distorts the terrestrial internal magnetic field at the surface, and this disturbance strongly affects the strength of a magnetic storm. The contribution of energetic ions (>40 keV) and of heavy ions to the total plasma pressure in the near‐Earth plasma sheet is not always considered. In this study, we evaluate the contribution of low‐energy and energetic ions of different species to the total plasma pressure for the storm observed by the Cluster mission from 27 September until 3 October 2002. We show that the contribution of energetic ions (>40 keV) and of heavy ions to the total plasma pressure is ≃76–98.6% in the ring current and ≃14–59% in the magnetotail. The main source of oxygen ions, responsible for ≃56% of the plasma pressure of the ring current, is located at distances earthward of XGSE ≃ −13.5 R E during the main phase of the storm. The contribution of the ring current particles agrees with the observed D s t index. We model the magnetic storm using the Space Weather Modeling Framework (SWMF). We assess the plasma pressure output in the ring current for two different ion outflow models in the SWMF through comparison with observations. Both models yield reasonable results. The model which produces the most heavy ions agrees best with the observations. However, the data suggest that there is still potential for refinement in the simulations. Plain Language Summary: Magnetospheric plasma sheet ions drift toward the Earth and populate the ring current. The ring current plasma pressure distorts the terrestrial internal magnetic field at the surface and strongly affects the strength of a magnetic storm. The contribution of energetic ions and of heavy ions to the total plasma pressure in the near‐Earth plasma sheet is not always considered. In this study, we evaluate the input of these components for the storm observed from 27 September until 3 October 2002 using observations by the Cluster mission. We compare the results with simulations from the Space Weather Modeling Framework which take into account ionospheric ion outflow. We show that neglecting the contribution of energetic ions and of heavy ions to the total plasma pressure can lead to the pressure underestimations of 76–98.6% in the ring current and 14–59% in the magnetotail. We find that it is important to consider heavy ions, especially ionospheric oxygen, and include the energetic part of the ion distribution in the simulations of the ring current and the magnetotail during the magnetic storm. Key Points: The contribution of ions of different species to the total plasma pressure in the near‐Earth magnetosphere is estimated The ability of the Space Weather Modeling Framework to reproduce the plasma pressure during a magnetic storm is tested The main source of oxygen ions is located at distances closer than XGSE = −13.5 R E during the main phase